Results of the First Attempt to Attract a Pair of the White-Tailed Eagles to an Artificial Nest - Altai Zh. Zhatkanbaev; Nurlan M. Dosov; Aleksey A. Grachev; Ermek S. Musyrpanov (Пернатые хищники и их охрана)
The White-Tailed Sea Eagle (Haliaeetus albicilla) is a large bird of prey native to the Southern shore of Lake Balkhash. In 2021, a pair of White-Tailed Sea Eagles nested in a try Poplar tree (Populus diversifolia) located 7.5–8 km southwest-southwest of the village of Karaoi, Balkash district, Almaty oblast, and raised two chicks. The nesting site was located in an a transitional biome containing characteristics of wetlands closer to the Ile River delta, and typical desert biotopes of the Southern Lake Balkhash. The nest was located in a cluster of poplar trees, only a few of which had relatively high height and trunk capacity, and only one of which was suitable for a large nest. The nest site was annually rebuilt and successfully used for brooding by eagles for over 10 reproductive seasons. The nesting site is located on "Duman-Ai" farm. There are no other poplar trees suitable for nesting within a 10km radius of the nest.